2-(Benzo[d]thiazol-2-yl) phenyl-4-nitrophenyl alkyl/aryl substituted phosphoramidates: Synthesis, characterization and antimicrobial activity evaluation. (4th March 2018) - Reddy, S. Munichandra; Rao, D. Subba; Madhu, K.; Subramanyam, Ch.; Kumari, P. Gnana; Raju, C. Naga
GRAPHICAL ABSTRACT: ABSTRACT: A series of new 2-(benzo [d] thiazol-2-yl) phenyl-4-nitrophenyl alkyl/aryl substituted phosphoramidate derivatives (7a-j ) of biological interest are synthesized in two steps via an in situ process without the isolation of the intermediate. 2-(Benzo [d] thiazol-2-yl) phenol(3) was treated with 4-nitrophenyl phosphorodichloridate(4) to obtain the monochloro intermediate, 2-(benzo [d] thiazol-2-yl)phenyl (4-nitrophenyl) phosphorochloridate(5). It was subsequently reacted with various amines, 6(a-j) to afford the desired title products. IR, NMR ( 1 H, 13 C and 31 P), mass spectral and elemental analysis are used to characterize the structures of the newly synthesized compounds. The antibacterial and antifungal activities are determined by the growth of inhibition of bacteria and fungi of the title compounds at two concentrations, 50 and 100 µg/mL, and minimum inhibitory concentrations to the active compounds. The compounds7e, 7f and7j exhibited promising inhibition activity against bacterial strains and7c, 7e and7i against A. niger and C. albicans and MIC values are in the range of 10.0–15.0 µg/mL.